Feasibility of marine renewable energies in African coastal countries - Lam, Wei Haur; Oppong, Stephen (International Journal of Renewable Energy Development)
Africa has 38 coastal countries with a population of 895,609,564 persons with potential to harness energy from ocean. These coastal countries are: Madagascar, South Africa, Mozambique, Angola, Namibia, Mauritius, Republic of Congo and Democratic Republic of Congo in Southern Africa with 25.31% population; Somalia, Eritrea, Tanzania, Sudan, Kenya, Seychelles, Comoros and Djibouti in Eastern Africa with 17.58% population; Egypt, Morocco, Libya, Tunisia and Algeria in Northern Africa with 20.96% population; Cape Verde, Gabon, Nigeria, Mauritania, Liberia, Ghana, Senegal, Cote d’Ivoire, Cameroon, Sierra Leone, Guinea Bissau, Guinea, Equatorial Guinea, Sao Tome and Principe, Benin, Gambia and Togo with population of 35.15%. Offshore wind, offshore solar, Tidal power, Wave energy, Salinity gradient, Ocean Thermal Energy Conversion (OTEC) are discussed with opportunities and challenges.